Residual Stress Measurements on the TIG Weld Joint of 57Fe15Cr25Ni Austenitic Steel for Structural Material Applications by Means X-Ray Diffraction Techniques - Parikin, Parikin; Ismoyo, Agus Hadi; Iskandar, Riza; Dimyati, Arbi (Makara Journal of Technology, 2017)
Measurements of residual stress on the 57Fe25Cr15Ni steel plate with no-filler TIG-welding process were carried out. This work was conducted to determine the nature of weld ability in synthesized steel. The bulks were formed in a dimension of 30x20x7 mm3 to ease data retrieval. Results show that the largest residual stress occurred in the weld metal area, amounting to 82.40 MPa with lattice stretching of 0.18%. Conversely, the values decreased to 65.92 MPa and a stretch of 0.14% in the HAZ area. This residual stress is a tensile stress that can reduce the mechanical strength of the material since it adds to the applied loads. This was confirmed by microstructure observations. The carbon content was very high in the dark lines. Weaken materials usually start from this side and could initiate the intergranular cracks that rapidly migrate among its grain boundaries.